Experimental sepsis‐induced mitochondrial biogenesis is dependent on autophagy, TLR4, and TLR9 signaling in liver. Issue 12 (27th August 2013) - Carchman, Evie H.; Whelan, Sean; Loughran, Patricia; Mollen, Kevin; Stratamirovic, Sladjana; Shiva, Sruti; Rosengart, Matthew R.; Zuckerbraun, Brian S.
Abstract : Organ injury in sepsis is initially characterized by dysfunction without cell death and structural damage, and thus with the ability to recover organ function. Adaptive metabolic responses to sepsis can prevent bioenergetic failure and death. These studies were aimed at investigating the influence of sepsis on mitochondrial homeostasis, focusing on removal of dysfunctional mitochondria and restitution of a healthy mitochondrial population. These data demonstrate decreased hepatic oxidative phosphorylation by 31 ± 11% following murine cecal ligation and puncture (CLP) at 8 h and 34 ± 9% following LPS treatment in vitro at 12 h ( P <0.05). In addition, there was a loss of mitochondrial membrane potential. Mitochondrial density and number initially decreased (relative area per micrograph of 64±10% at baseline vs. 39±13% at 8 h following LPS; P <0.05) and was associated with an increase in autophagy and mitophagy. CLP‐induced markers of mitochondrial biogenesis and mitochondrial number and density recovered over time. Furthermore, these data suggest that mitochondrial biogenesis was dependent on an autophagy and mitochondrial DNA/Toll‐like receptor 9 (TLR9) signaling pathway. These results suggest that hepatocyte survival and maintenance of function in sepsis is dependent on a mitochondrial homeostasis pathway marked by mitophagy and biogenesis.—Carchman, E. H., Whelan, S., Loughran, P., Mollen, K., Stratamirovic, S., Shiva, S., Rosengart, M. R., Zuckerbraun, B. S., Experimental sepsis‐induced mitochondrial biogenesis is dependent on autophagy, TLR4, and TLR9 signaling in liver. FASEB J. 27, 4703–4711 (2013). www.fasebj.org